Protein transport and flagellum assembly dynamics revealed by analysis of the paralysed trypanosome mutant snl-1. - Bastin, P; Pullen, T; Sherwin, T; Gull, K (1999)
The paraflagellar rod (PFR) of Trypanosoma brucei is a large, complex, intraflagellar structure that represents an excellent system in which to study flagellum assembly. Molecular ablation of one of its major constituents, the PFRA protein, in the snl-1 mutant causes considerable alteration of the PFR structure, leading to cell paralysis. Mutant trypanosomes sedimented to the bottom of the flask rather than staying in suspension but divided at a rate close to that of wild-type cells. This phenotype was complemented by transformation of snl-1 with a plasmid overexpressing an epitope-tagged copy of the PFRA gene. In the snl-1 mutant, other PFR proteins such as the second major constituent, PFRC, accumulated at the distal tip of the growing flagellum, forming a large dilation or 'blob'. This was not assembled as filaments and was removed by detergent-extraction. Axonemal growth and structure was unmodified in the snl-1 mutant and the blob was present only at the tip of the new flagellum. Strikingly, the blob of unassembled material was shifted towards the base of the flagellum after cell division and was not detectable when the daughter cell started to produce a new flagellum in the next cell cycle. The dynamics of blob formation and regression are likely indicators of anterograde and retrograde transport systems operating in the flagellum. In this respect, the accumulation of unassembled PFR precursors in the flagellum shows interesting similarities with axonemal mutants in other systems, illustrating transport of components of a flagellar structure during both flagellum assembly and maintenance. Observation of PFR components indicate that these are likely to be regulated and modulated throughout the cell cycle.